The Benthic Foraminiferal Assemblages in the Seagrass Bed of Tanjung Berakit Waters, Bintan Island - Suhartati M. Natsir; Ira Dillenia (HAYATI Journal of Biosciences, 2023)
Seagrass is the most common ecosystem in Tanjung Berakit waters. Therefore, Tanjung Berakit waters have a very important role as a benthic foraminiferal habitat. This study was conducted to describe the distribution of benthic foraminifera relating to the environmental condition of the waters. The samples were collected from eight stations by handling garb in November 2017. This study collected 18 species of shallow water benthic foraminifera dominated by Amphistegina and Heterostegina. This study recorded a correlation between the sediment texture and foraminiferal assemblages. The most common foraminifera were inhabiting fine-textured sediments, especially very fine sand and silt. Only a few foraminifers are collected from extremely fine sediments such as clay sediments, or extremely coarse including pebbles.